Edible bird’s nest (EBN) ameliorates the effects of Indomethacin (IMC) -induced embryo implantation dysfunction in rats - Amir, Maria; Yimer, Nurhusien; Hiew, Mark; Mohd Yusoff, Md Sabri; Mohammed Babatunde, Sadiq; Quddus, Abdul (Multidisciplinary Digital Publishing Institute, 2025)
Indomethacin (IMC) is a nonsteroidal anti-inflammatory drug (NSAID) and a pharmaceutical product that is embryotoxic and leads to disruption of the implantation process when administered at doses higher than the therapeutic limit. IMC can cause infertility in animals and humans through inhibition of cyclo-oxygenase enzymes (COX), which are important in the synthesis of implantation mediating prostaglandins, and disruption of growth factors and steroid hormone receptors. Our results revealed that rats administered with a higher dose of EBN exhibited remarkable protective effects against IMC-induced toxicity on fertility and reproductive performance, thus highlighting the role of an edible bird’s nest in mitigating the impact of IMC on uterine tissues. IMC has been reported to influence embryo implantation negatively in animals including rats. While EBN has been known to have a potential protective effect against reproductive toxicity, there is limited study on the effect of EBN on IMC toxicity in reproduction. This study aimed to ascertain whether pretreatment with a natural substance, Edible Bird’s Nest (EBN), will reduce IMC-induced toxicity in pregnant rats. Thirty Sprague-Dawley rats divided into five equal groups were treated with EBN and IMC as follows: G1 = Control, G2 = IMC (4.33 mg/kg), G3 = IMC + EBN (4.33 mg/kg + 60 mg/kg), G4 = IMC + EBN (4.33 mg/kg + 90 mg/kg), and G5 = IMC + EBN (4.33 mg/kg +120 mg/kg). EBN was administered once daily for 8 weeks while IMC was injected subcutaneously. On day 8 after mating, all rats were sacrificed for blood sampling and embryo implantation rate (EIR) assessment; the uterine tissues were also subjected to immunohistochemical and histological analyses. G5 recorded significantly higher EIR, fertility index, and expression of epidermal growth factor receptor (EGFR) in the uterine section, across stroma cells, the glandular epithelium, and the luminal epithelium compared to control and other groups. IMC-induced inflammatory alterations, endometrial atrophy, vacuolar degeneration, and atrophy were not detected in uterine tissue sections in G4 and G5, with the latter group demonstrating the highest EIR with protective effects on uterine tissues. Thus, EBN supplementation might be of great benefit in guarding the fertility of individuals who depend on IMC for the treatment of chronic inflammatory illness.